SARS-CoV-2 genomes from Saudi Arabia implicate nucleocapsid mutations in host response and increased viral load - Mourier, Tobias; Shuaib, Muhammad; Hala, Sharif; Mfarrej, Sara; Alofi, Fadwa; Naeem, Raeece; Alsomali, Afrah; Jorgensen, David; Subudhi, Amit Kumar; Ben Rached, Fathia; Guan, Qingtian; Salunke, Rahul P.; et al. (Nature communications, 2022)
Monitoring SARS-CoV-2 spread and evolution through genome sequencing is essential in handling the COVID-19 pandemic. Here, we sequenced 892 SARS-CoV-2 genomes collected from patients in Saudi Arabia from March to August 2020. We show that two consecutive mutations (R203K/G204R) in the nucleocapsid (N) protein are associated with higher viral loads in COVID-19 patients. Our comparative biochemical analysis reveals that the mutant N protein displays enhanced viral RNA binding and differential interaction with key host proteins. We found increased interaction of GSK3A kinase simultaneously with hyper-phosphorylation of the adjacent serine site (S206) in the mutant N protein. Furthermore, the host cell transcriptome analysis suggests that the mutant N protein produces dysregulated interferon response genes. Here, we provide crucial information in linking the R203K/G204R mutations in the N protein to modulations of host-virus interactions and underline the potential of the nucleocapsid protein as a drug target during infection. In this study, the authors sequence 892 SARS-CoV-2 genomes from Saudi Arabia and describe population dynamics and importations into the country. They identify a nucleocapsid protein mutation associated with increased viral load and host interactions and characterise its role through biochemical analyses.